Migrating art: a research design to support refugees' recovery from trauma – a pilot study. Issue 2 (3rd July 2017) - Rose, Emma; Bingley, Amanda
ABSTRACT: An international challenge is presented by the unprecedented number of refugees worldwide, many of whom have undergone psychological and social stresses associated with migration and who consequently experience mental health disorders. A growing number of organizations recognize the role of art in supporting refugees to support recovery from trauma, and this pilot study in participatory arts is designed to contribute to the field. The research was undertaken with a charity supporting pre- and post-natal women refugees who are victims of rape, trafficking, sexual violence, domestic servitude and other forms of gender based violence and human rights abuses. The research explores the benefits of painting landscapes through re-imagining places experienced as a 'safe-haven', or journey towards safety. The research design is explored with a view to inform a further research study using the approach to evaluate a participatory arts workshop model that support refugees' recovery and transition.